PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEPUASAN KERJA DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING - ERVYANA FITRI (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
ABSTRACT The purpose of this study is to describe: (1) the influence of transformational force on job satisfaction; (2) the influence of the transformational leadership style on organizational commitment; (3) the influence of organizational commitment to job satisfaction; (4) the influence of transformational leadership style on job satisfaction with organizational commitment debagai intervening variable. This research is a quantitative research. Population in this research is employees